The Protection Policies on Predatory Digital Credit Traps Students: Lessons from Indonesia - Ali Masyhar; Pupung Purnawarman; Nunung Suryati; Sri Setyarini; Muhammad Azam (Journal of Human Rights, Culture and Legal System, 2026)
This study examines the increasing practice of illegal online lending that targets university students and places them in financially vulnerable conditions. The rapid growth of digital lending services has expanded access to credit, but it has also enabled predatory schemes that exploit students with limited income and insufficient financial literacy. This research aims to analyze the factors that encourage student involvement in illegal online lending, identify the operational patterns adopted by unlawful lenders, and formulate effective measures for risk protection. The study uses a sociolegal approach that combines normative legal analysis with empirical data gathered through questionnaires and interviews with students. The findings show that, first, many students understand that online loans do not offer sustainable solutions to financial difficulties, yet many remain unable to distinguish lawful platforms from unlawful services. Second, financial pressure, immediate access to funds, persuasive digital promotion, and limited awareness of legal risks significantly increase student exposure to illegal lending. Third, illegal lenders impose excessive charges, misuse personal data, employ coercive collection methods, and generate financial instability, psychological distress, and declining academic performance. This study concludes that student vulnerability to illegal online lending reflects a structural problem that requires stronger regulation, university-based protection mechanisms, and continuous financial literacy programs.